2013
DOI: 10.1111/jocn.12262
|View full text |Cite
|
Sign up to set email alerts
|

Adult men's beliefs, values, attitudes and experiences regarding contraceptives: a systematic review of qualitative studies

Abstract: A deeper male consciousness regarding contraceptive responsibility should be promoted. It requires the knowledge of the men's personal backgrounds regarding contraceptives because they can be diverse according to family, social and cultural contexts. The consideration of the men's personal perspective is essential in the planning and implementation of reproductive health care. These aspects are essential for the concretisation of the evidence-based health care, a current challenge worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 44 publications
1
20
0
3
Order By: Relevance
“…Although some studies have investigated men's involvement in family planning decisions [13][14][15][16][17][18], the focus on women of most analyses of contraceptive practices suggests that men are not really considered to be part of the "contraceptive story." Men's sexuality is widely explored, but studies of their contraceptive practices are scarce [19][20][21] and most often focus on the concordance of men's and women's descriptions of current contraceptive use [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have investigated men's involvement in family planning decisions [13][14][15][16][17][18], the focus on women of most analyses of contraceptive practices suggests that men are not really considered to be part of the "contraceptive story." Men's sexuality is widely explored, but studies of their contraceptive practices are scarce [19][20][21] and most often focus on the concordance of men's and women's descriptions of current contraceptive use [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…O hâlde sağlık personelinin kadınları hizmet almaya eşleri ile gelmeye teşvik etmeleri ve erkeklerin katılımına yönelik daha başka stratejiler geliştirmeleri gerekmektedir. 25 Bu çalışmada, hemşirelerin deneyimleri, eği-tim düzeyi düşük ve gelir getiren herhangi bir işte çalışmayan kadınların yönteme ulaşma, kendini ifade etme, kendi bedeninin sorumluluğunu alma konularında sorun yaşadığını ve geri çekme yönte-mini daha fazla kullandığını göstermektedir. Düşük sosyoekonomik düzey ve eğitim düzeyi, kırsal alanda ve doğu bölgesinde yaşıyor olma daha fazla oranda geri çekme yöntemi kullanımı ile ilişkili bulunmuştur.…”
Section: Discussionunclassified
“…Sözü edilen bu durum, AP hizmetlerini planlarken erkeklere yönelik farklı stratejilere gereksinim duyulduğunu ortaya koymaktadır. 25,31,32 …”
Section: Discussionunclassified
“…Hoga et al (2014) found sixteen qualitative studies eligible for inclusion in their systematic review undertaken to facilitate the recommendation of the UN Conference on Population and Development held in Cairo in 1994, which sought to increase contraceptive access globally and also attempted to legalize universal access to abortion. The review found that religion, family, and social background are strong influences on contraceptive use, and that men's acceptance of contraceptive responsibility was highest among Protestant Christians who were most likely to make use of condoms and vasectomy from a sense of responsibility for their families.…”
Section: Impact On Spiritualitymentioning
confidence: 99%
“…The review found that religion, family, and social background are strong influences on contraceptive use, and that men's acceptance of contraceptive responsibility was highest among Protestant Christians who were most likely to make use of condoms and vasectomy from a sense of responsibility for their families. These usages were not without ambivalence, which healthcare providers must deal with if contraceptive use is to expand (Hoga et al 2014). …”
Section: Impact On Spiritualitymentioning
confidence: 99%